Childhood cancers in a referral hospital in northern Nigeria - Mohammed, A; Aliyu, H O (Indian Journal of Medical and Paediatric Oncology, 2009)
Background:We undertook this study to determine the relative frequencies of childhood malignancies and their age - sex distribution in this environment.Materials and Methods:Hospital-based data of histological and cytologically confirmed cases of malignancies in children, aged ≤ 15 years, was collated over a period of 11 years, from the Cancer Registry.Results:A total of 329 children aged ≤ 15 years, with confirmed malignant disease, was recorded. This constituted 8.44% of all malignancies diagnosed in the same period with a Male : Female ratio of 1.5:1. Burkitt′s lymphoma accounted for 27.01% of the cases followed by retinoblastoma (17.02%), non-Hodgkin′s non-Burkitt′s Lymphoma (9.42%), and Rhabdomyosarcoma (9.42%). Others were Nephroblastoma (8.81%), Hodgkin′s lymphoma (6.69%), Neuroblastoma (3.34%), Colorectal carcinoma (2.43%), Osteosarcoma (2.13%), and Unspecified lymphomas (1.82%). Burkitt′s lymphoma was most prevalent in the 5-9 and 10-15 year age groups, retinoblastoma in the 0-4 year age group, and Non-Hodgkin′s lymphoma, Hodgkin′s lymphoma, and unspecified carcinomas were more prevalent in the 10-15 year age group.Conclusion:Lymphomas were the most prevalent malignancies of childhood seen in this region and the majority were of the Burkitt type, in contrast to the predominant leukemic and central nervous system trend seen in developed nations.
Keywords: Childhood cancers; lymphoma; Nigeria